Suppression of inflammatory mediators by aqueous leaf extract of Crotalaria verrucosa: in vivo and in vitro analysis - Billah, Mohammad Mustakim; Huzaifa, Abir; Khan, M. Abdul Kader; Vabna, Nusrat Jahan; Nawrin, Kashfia; Rayhan, M. Abu (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Crotalaria verrucosa is a traditional plant frequently prescribed by the tribes for its medicinal value against inflammation. The present study was designed to investigate the scientific basis for medicinal value in inflammation by in vivo and in vitro analysis. Methods: Anti-inflammatory activity of the plant’s leaf was evaluated by two in vivo methods - carrageenan induced rat paw edema and xylene induced mice ear edema. Moreover, in vitro analysis was performed through heat induced hemolysis and heat induced protein denaturation methods. Results: The inflammation produced by carrageenan and xylene were effectively suppressed by the aqueous leaf extract of C. verrucosa (CVAQ) at 600 mg/kg body weight which was comparable to the standards. In heat induced hemolysis test the extract was able to inhibit the lysis up to 70% at 500 µg/ml whereas in heat induced protein denaturation test it reduces the percentage till 69% at the same concentration. Conclusions: The findings suggested that CVAQ possess moderate to high anti-inflammatory activity when applied in low to high concentrated doses. However, the study can only conclude from this basic evaluation that the extract needs to be further investigated for identifying the potential compound which contributed to such medicinal value of the plant.